Informační potřeby a informační chování učitelů na základních školách v průběhu pandemie Covid-19 - Kubálková, Natálie (Univerzita Karlova, Filozofická fakulta, 2023)
The aim of the diploma thesis is to analyze and compare information needs and information behavior of primary school teachers during the Covid-19 pandemic. The theoretical part of the thesis will focus on information behavior of teachers and will describe the development of anti- epidemic measures in education during the coronavirus pandemic. The practical part will be based on a combination of questionnaires, depth interviews and their subsequent evaluation. The thesis will focus on the information behavior of teachers, processing use of information, information sources, evaluation of the credibility of the information sought by teachers in preparation for teaching, in teaching itself and in self-education. The thesis also aims to find out how teachers themselves evaluate information and information sources of pupils in reports and school work in the period before the pandemic and then during it. Diploma thesis will be prepared according to valid inner regulations of Faculty of Arts, Charles University and further guidelines and normative documents. Keywords information behavior, information needs, information evaluation, information seeking, teachers, Covid-19 pandemic Cílem diplomové práce je zanalyzovat a porovnat informační potřeby a informační chování učitelů na základních školách v průběhu pandemie Covid-19. Teoretická část diplomová práce se bude zabývat informačním chováním učitelů a popíše rovněž vývoj protiepidemických opatření ve školství během pandemie koronaviru. Výzkumná část bude založena na kombinaci dotazníků, hloubkových rozhovorů a jejich následného vyhodnocení. Zaměří se na informační chování učitelů, zpracování, používání informací, informační zdroje, hodnocení věrohodnosti vyhledávaných informací učiteli při přípravě na vyučování, v samotném vyučování a při sebevzdělávání. Práce má dále za cíl zjistit, jak sami učitelé hodnotí informace a informační zdroje žáků v referátech a školních pracích v době před pandemií a poté v jejím průběhu. Diplomová práce bude připravena v souladu s ...